HASIL BELAJAR KETERAMPILAN SOSIAL SAINS FISIKA MELALUI MODEL PEMBELAJARAN GENERATIF PADA SISWA KELAS VIII B3 MTs DAR EL HIKMAH PEKANBARU - M. Rahmad; Aflina Sari Dewi (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2007)
The purpose of the research is to describe learning result of social skill science physics throughGenerative Learning Model in MTs Dar El Hikmah Pekanbaru. This Research was run from December 2006up to June 2007. Subjek in this research is class student of VIII B3 amounting to 30 men student. Thisresearch taken only selected of 10 students at random to be perceived. The instrument of this research consistof study instrument and data collecting instrument. The collecting data use observation sheet and its dataanalysis through percentage technique. From data analysis result of learning skill of high social that isstaying in duty ( 80.5 %), taking turn and sharing duty ( 55.2 %), while lowest at aspect push participation(19,5%). Therefore, applying of effective Generative Learning Model enough to increase social skill ofscience physics at sound items.Keyword : Generative Learning Model, social skill